Portomesenteric Venous Thrombosis Post-Laparoscopic Sleeve Gastrectomy: Do Energy Systems Pose as Instigating Factor to This Infrequent Complication? - Bani Hani, Mohammed N (Clin Med Insights Case Rep, 2019)
BACKGROUND: Portomesenteric venous thrombosis (PMVT), a rare complication after laparoscopic sleeve gastrectomy (LSG). Severe consequences are owed to a high risk of bowel ischemia. Our aim is to present a series of patients who developed PMVT after LSG, highlighting the potential role of the vessel sealer and divider as a risk factor. METHODS: Medical records of seven patients who underwent LSG and developed PMVT from April 2010 to January 2019, at King Abdullah University Hospital and Jordan University Hospital, Jordan were reviewed. Our findings were studied, audited, and compared with published data. RESULTS: A sum of 4900 patients underwent LSG, 7 (0.14%) developed PMVT. The mean age and body mass index (BMI) were 36.8 years and 45 kg/m(2), respectively. Four were women. Epigastric pain radiating to the back was the presenting symptom at a median time of 9 days after surgery. Computed tomography (CT) of the abdomen confirmed the diagnosis. Five patients presented with a total portal vein thrombosis (PVT), one with splenic vein thrombosis and one with dual portal and mesenteric vein thrombosis. CONCLUSION: Portomesenteric venous thrombosis is a relatively uncommon complication following LSG. Early recognition is required to avoid catastrophic outcomes. The role of energy systems in the development of PMVT remains unknown and requires further elaboration.